The effects of the COVID-19 pandemic on vocational education and training in Germany - Dummert, Sandra [Verfasser]; Umkehrer, Matthias [Verfasser] (My University, 2025)
„In this paper, we investigate the effects of the COVID-19 pandemic on vocational education and training in Germany. We exploit rich establishment-level survey data to estimate the causal effects of the pandemic by applying difference-in-differences estimation, contrasting trends in outcomes between establishments that suffered to varying degrees from adverse economic impacts after the first lockdown. We find that, due to the pandemic, establishments have not become more likely to leave the training market but hired less new trainees and retained less of their recent graduates in the first two years of the crisis, on average. We also compare these effects with the effects of the Great Recession on training and find that both are remarkably similar. Our findings foster concerns that the pandemic increases future skills shortage in the labour market and dampens young peoples’ career prospects.“ (authors’ abstract; BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; S 3.2 Unternehmen und Behörden; 370; Berufsausbildung; Pandemie; Auswirkung; Betrieb; Ausbildungsverhalten; Fachkräftemangel